A new species of the genus Gasterocercus (Coleoptera, Curculionidae, Cryptorhynchinae) from the Iberian Peninsula, with notes on the ecology of the genus - Alonso-Zarazaga, Miguel A.; Jover, Teresa María; Micó, Estefanía (Zootaxa, 2009)
Gasterocercus hispanicus, a new species of the genus Gasterocercus Laporte & Brullé, 1828 is described from the Iberian Peninsula. Until now, Gasterocercus depressirostris (Fabricius, 1793) was the only European species of the genus, which includes 9 species distributed in the Palaearctic, Oriental and Australian realms and lives on dead wood or in dying trees. We summarise the known biological information for both European species, providing new data on the ecology of the genus.